Music therapy and music cognition: parallel fields - Goldschmidt, Daniel, author (Colorado State University. Libraries, 2017)
The current project is building a connection between the fields of music therapy and music cognition. Music therapists research and practice evidence-based musical interventions to reach non-musical goals with clients in many different populations. Music cognition is a field learning about cognitive, perceptual, and behavioral aspects of music and humanity. While seemingly similar, they are frequently detached despite asking similar questions. My goal is to go forward and educate music therapists, the public, possible employers, and other health professionals on utilizing music neuroscience research in practice. By working in partnership these two fields can do the most good for humanity.
117 - Daniel Benjamin Goldschmidt
Poster featured at the 2017 CSU Gradshow, and won an award from the Graduate Student Council.
Keywords: music therapy; music cognition